STUDENTS LEARNING MOTIVATION IN STUDYING ENGLISH AT SMP AL-QURAN PUTRA BAHARI KOTA TERNATE - Niar Zulkifli; Fitria Wulan Sari; Saiful Latif (Universitas Khairun, 2022)
This study aims to determine students' learning motivation in studying English. The motivation of this research is divided into intrinsic and extrinsic motivations. This study uses quantitative descriptive research. The research population is class 2A and 2B. The sample of this research is class 2B consisting of 23 students, with the instruments of observation, questionnaire, interview, and documentation. In conclusion, Students' Learning Motivation in Studying English at SMP Al-Qur'an Putra Bahari Kota Ternate in class 2B is more influenced by extrinsic motivation (271). Based on the results of the research, generally, the students of SMP Al-Qur'an Putra Bahari Kota Ternate do not have an awareness of the learning experience so the intrinsic motivation of these students is low, as we know that in general English learners are students who are in the category of instrumental motivation. Therefore, the extrinsic factor is more dominant to spur students' enthusiasm for learning while integrative motivation is not comparable to instrumental motivation. This motivation is the reason why students especially students of SMP Al-Quran Putra Bahari Kota Ternate have an intrinsic motivation that is not comparable to extrinsic motivation.